Management in Islamic Countries - Husein, UmmeSalma Mujtaba (Business Expert Press, 2014)
Ebook from IG Library ; Up until now, much of the Islamic perspectives discussed and published center around understanding Islamic finance and banking. Given that Islam is an all-encompassing code of conduct and offers insight on all aspects of life, there is clearly a need for more all-encompassing academic content related to topics other than Islamic finance.